Cochrane Database of Systematic Reviews 2005
DOI: 10.1002/14651858.cd002007.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Single versus combination intravenous antibiotic therapy for people with cystic fibrosis

Abstract: Single versus combination intravenous antibiotic therapy for people with cystic fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(13 citation statements)
references
References 48 publications
1
9
1
1
Order By: Relevance
“…For the former, the three existing studies indicate no mortality benefit with wide CIs (RR = 0.43, 95% CI 0.12-1.57) and for the latter no studies exist. A previous systematic review summarised the evidence for patients with CF, analysing the outcomes relevant for this patient population that were outside the scope of the current review [12]. There was no benefit to combination therapy with regard to lung function, symptom scores, bacterial eradication and resistance development in existing trials, but there were major limitations in the evidence found related to the paucity of trials and the variability of outcomes reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the former, the three existing studies indicate no mortality benefit with wide CIs (RR = 0.43, 95% CI 0.12-1.57) and for the latter no studies exist. A previous systematic review summarised the evidence for patients with CF, analysing the outcomes relevant for this patient population that were outside the scope of the current review [12]. There was no benefit to combination therapy with regard to lung function, symptom scores, bacterial eradication and resistance development in existing trials, but there were major limitations in the evidence found related to the paucity of trials and the variability of outcomes reported.…”
Section: Discussionmentioning
confidence: 99%
“…Systematic review and other overviews have tried to compile existing clinical evidence on the effects of combination therapy [4][5][6][7][8][9][10][11][12]. In general, meta-analyses of observational studies have shown a benefit for combination therapy [8,11], whilst those including randomised controlled trials (RCTs) have not [4][5][6][7]9,10,12]. These reviews approached the question from different perspectives, each addressing a specific clinical scenario [Gram-negative bacteraemia, febrile neutropenia, empirical treatment of sepsis, endocarditis, ventilator-associated pneumonia, cystic fibrosis (CF)], with different study designs, different definitions of combination therapy and different outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…In a Cochrane meta-analysis from 2005 comparing monotherapy versus combination therapy for patients with cystic fibrosis exacerbations, the authors determined that there was insufficient evidence to conclusively determine the effects of the different treatment approaches on the emergence of resistance to P. aeruginosa (67). In summary, the theoretical advantage of minimizing emergence of resistant mutants has not been confirmed conclusively in clinical studies.…”
Section: Prevention Of Resistancementioning
confidence: 99%
“…As there have been a number of studies conducted to assess the appropriateness of combination therapy for infections caused by Gram-negative organisms, several meta-analyses have been compiled to summarize these data (Table 1) (23,67,68,80,161,194,(196)(197)(198)(199)212). In general, meta-analyses of observational studies have shown a benefit of combination therapy, while those including RCTs have not demonstrated such a benefit (161).…”
Section: Meta-analysesmentioning
confidence: 99%
“…However, some of the major problems associated with gentamicin include drugresistant pathogens harbouring aminoglycoside-modifying enzymes as well as severe renal and neuromuscular toxicity [13]. Gentamicin is traditionally given through intravenous injection [14,15] liposome delivery systems are being utilised in an effort to reduce the drug-associated toxicity while enhancing efficacy [16][17][18].…”
Section: Introductionmentioning
confidence: 99%